2019
DOI: 10.1177/1362168819856451
|View full text |Cite
|
Sign up to set email alerts
|

One size fits all? In search of the desirable caption display for second language learners with different caption reliance in listening comprehension

Abstract: Existing research has established captions as effective second-language (L2) or foreign language (FL) listening comprehension aids. However, due to the transient nature of captions, not all learners are capable of attending to captions in all cases. Previous work posited that to leverage the impact of technologies in learning and instruction, a better understanding of the interplay between technology and cognition is warranted. In this vein, the current study set out to investigate the effects of four differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Similar findings regarding the effects of keyword captions were reported by Teng (2019a) in a study with primary school learners. Additionally, Lee et al (2021) took into account learners’ self-reported caption reliance (i.e., how much they rely on captions while watching video) when comparing the effects of full, partial, and no captions on L2 learners’ comprehension. It was found that learners in a high captioning reliance group (see Section 6.2) performed best on a comprehension test after watching an 11-minute TED-talk with full captions (as compared with partial and no captions).…”
Section: Comprehension Of L2 Audio-visual Input and The Role Of On-sc...mentioning
confidence: 99%
“…Similar findings regarding the effects of keyword captions were reported by Teng (2019a) in a study with primary school learners. Additionally, Lee et al (2021) took into account learners’ self-reported caption reliance (i.e., how much they rely on captions while watching video) when comparing the effects of full, partial, and no captions on L2 learners’ comprehension. It was found that learners in a high captioning reliance group (see Section 6.2) performed best on a comprehension test after watching an 11-minute TED-talk with full captions (as compared with partial and no captions).…”
Section: Comprehension Of L2 Audio-visual Input and The Role Of On-sc...mentioning
confidence: 99%
“…Specifically, post-study retrospection can allow a researcher to accurately report on one's modality preference in real-time video processing only when and if swift processing of video content is reliably open to consciousness. However, as seen in Lee et al (2019), L2 learners' modality preference while viewing the video material is not always consistent with their offline verbal report conducted after the video viewing task. Lee et al found that notwithstanding L2 learners' superior performance under the partial captioning viewing conditionan indication of their preference for partial captioning while viewing the video materialsthey found captioning distracting in the post-study retrospective questionnaire.…”
Section: Preferred Modality and Its Potential Role In Modulating The mentioning
confidence: 85%
“…This study demonstrates the intimate relationship between modality reliance and multimodal L2 listening. Recently, drawing on the CRT, Lee et al (2019) examined whether learners' modality preference while viewing captioned videos affected their listening outcomes. Lee et al observed that due to different modality preference (visual vs. auditory), L2 learners showed differential reliance on captioned texts; this determined the extent to which L2 learners may have benefited from a captioning viewing environment (see also Hasler, Kersten & Sweller, 2007).…”
Section: Preferred Modality and Its Potential Role In Modulating The mentioning
confidence: 99%
See 2 more Smart Citations